Restoration of aged bitumen properties using maltenes - Putra Jaya, Ramadhansyah; Z. H., Hussein; Haryati, Yaacob; IM. K., Idham; Norhidayah, Abdul Hassan; Choy, L. J. (IOP Publishing Ltd, 2020)
Reclaimed asphalt pavement (RAP), a material frequently used in asphalt mixtures, is associated with several environmental and economic advantages. Many existing road construction technologies are capitalising on the availability of recycled materials. This study has looked on the usage of maltene as a rejuvenator in aged bitumen. Bitumen with Pen 60-70 was chosen as the control binder. Maltene was added into the aged bitumen at various concentrations (5%, 10%, and 15%) by weight of total binder. The characteristics of rejuvenated bitumen were examined with penetration, softening point, penetration index (PI), viscosity, and storage stability. As the maltene concentration increased, aged bitumen characteristics improved, while the level of stiffness reduced. Mixing temperature and time were significantly linked to the efficiency of blending between aged-virgin binders. Lower mixing temperatures undermined the diffusion of the virgin bitumen into the aged binder, thereby impairing blending efficiency. The results indicate that 15% of maltene can rejuvenate the properties of aged bitumen.